Tumor–Stroma Interactions Drive 3D Growth and Self-Organization in PDAC Spheroids: A Quantitative Study in Microfluidic Models - Hernandez, Soraya; Borau , Carlos; Martínez Bosch , Neus; Navarro, Pilar; García Aznar , José Manuel; Guerrero , Pedro Enrique (Jornada de Jóvenes Investigadores del I3A, 2025)
We present a microfluidic-based 3D model of pancretic cancer that reveals how tumor–stroma interactions and matrix mechanics govern spheroid self-organization. Using quantitative imaging, we uncover cell type–specific growth patterns and stromal responses. This platform advances in vitro modeling of pancretaic cancer heterogeneity and reveals biomechanical drivers of tumor architecture.